Comparison of Efficacy, Embolism Rate and Safety of Thrombectomy with Stent Retrievers in an Anterior Circulation Stroke Model - Larsen, Naomi; Oberbeck, Katharina; Lima de Miranda, Rodrigo; Trentmann, Jens; Madjidyar, Jawid; Quandt, Eckhard; Jansen, Olav (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose Various stent retrievers differing in stent design and mechanical properties are currently available for the treatment of ischemic stroke. We conducted this in vitro study to compare the efficacy, embolism rate, and safety of commercially available stent retrievers and prototypes.Materials and Methods Whole blood thrombi were produced in a Chandler loop. The thrombi were inserted into the curved M1 segment of a silicone model of the anterior cerebral circulation. Thrombectomy maneuvers were performed with six commercially available stent retrievers and 2 prototypes with different strut thickness. Wall-stent apposition, first pass recanalization rate, retraction force, and embolism rate were compared.Results Devices with complete wall-stent apposition had the highest first pass recanalization rate and lowest embolism rate, but showed the highest retraction force. The prototype with thinner struts had a comparable recanalization and embolism rate, while a lower retraction force had to be applied compared to the prototype with thicker struts.Conclusion Complete wall-stent apposition facilitates a higher recanalization rate and lower embolism rate but also correlates to a higher necessary retraction force and thus possibly higher risk of endothelium damage. Stent modifications leading to a reduced retraction force do not compromise efficacy and embolism rate.Key Points: Citation Format
Keywords: thrombectomy; stroke; stent retriever